2022
DOI: 10.1021/acs.jafc.2c00360
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Genes are Involved in Lambda-Cyhalothrin Resistance in Cydia pomonella via Sequestration

Abstract: Pest management is mostly accomplished by the use of insecticides. However, the overuse of insecticides has led to the development of resistance. Glutathione S-transferases (GSTs) are vital detoxification enzymes involved in insecticide resistance in insects. In this study, we report the involvement of GSTs in insecticide resistance to lambda-cyhalothrin in Cydia pomonella, a globally quarantined fruit pest. A total of 25 GST, including 22 cytosolic genes and 3 microsomal genes, are identified from the genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 51 publications
2
60
0
Order By: Relevance
“…A susceptible strain of C. pomonella (SS) is reared in the laboratory without insecticides exposure for more than 50 generations. 10 A field field-evolved lambda -cyhalothrin-resistant population (ZW_R) of C. pomonella 18 was used in this study. This strain was reared in the laboratory under the same conditions as the SS strain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A susceptible strain of C. pomonella (SS) is reared in the laboratory without insecticides exposure for more than 50 generations. 10 A field field-evolved lambda -cyhalothrin-resistant population (ZW_R) of C. pomonella 18 was used in this study. This strain was reared in the laboratory under the same conditions as the SS strain.…”
Section: Methodsmentioning
confidence: 99%
“…In almost all pome fruit-producing countries, effects to control the C. pomonella have mainly relied on synthetic insecticides such as lambda -cyhalothrin, particularly widely used. 5, 7, 8 However, with the extensive application of insecticides, field-evolved resistance has been widely documented in C. pomonella worldwide 1, 810 aside potential multiple occurring side effects of pesticides on non-target organisms. 11 The evolution of resistance to insecticides not only demonstrated the striking ability of this species to adapt to insecticides stress, which may explain its worldwide expansion, but also an ongoing challenge to sustainable management of this species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ability to ingest and tolerate toxic cardenolide strophanthidin by specialized biochemical mechanism involving GST in strophanthidin sequestration as glutathione-strophanthidin conjugate facilitating insect fitness. Recombinant soluble GST proteins and in silico simulation studies confirmed the interaction and conjugation reaction of GST proteins with λ-cyhalothrin insecticide as a means of tolerance mechanism in codling moth ( Hu et al., 2022 ). Molecular docking and dynamic results predict a stronger interaction between delta variant of GST and glutathione-strophanthidin conjugate (Figures 7 and 8 ).…”
Section: Discussionmentioning
confidence: 78%
“…GST enzymes of delta and epsilon subclasses are involved in the metabolism of λ-cyhalothrin insecticide in codling moth (Cydia pomonella) larvae (Hu et al, 2019;Wang et al, 2019). The expression levels of GST genes were upregulated on exposure to LD 10 dose of lambda-cyhalothrin in codling moth and the levels were considerably higher in lambda-cyhalothrin-resistant codling moth populations (Hu et al, 2022). HR-LC MS analysis of Olepa sps.…”
Section: Discussionmentioning
confidence: 99%